Simulation of the Power Flow of a Solar and Wind Hybrid Power Plant in the Situ Bunderan Garut Tourist Area - Rahmat, Saepul Rahmat; Purnata, Hendi; Sumardiono, Arif (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Solar and wind energy as renewable energy sources have great potential to be used as clean energy sources but are hampered by high installation operational costs, so a feasibility simulation study of the system model to be installed is needed to see whether it meets the criteria for safe and reliable power flow. This research aims to determine the power analysis of two types of renewable energy generators through power flow simulations for 14 IEEE system buses and contribute to the use of hybrid buses for wind power plants and solar power plants so that the use of renewable energy in interconnection with PLN energy sources can still be carried out because it meets the specified requirements. Based on the existing component data, modeling is carried out in the form of a single diagram of the electrical system which will be input to each parameter and run the simulation. The simulation results show that the voltage value on each bus still meets the input voltage safety tolerance limit of 105% for overvoltage and 95% for undervoltage. equipment connected to an energy source supplies active power according to the equipment specifications that have been determined and there is no critical or marginal failure in supplying the existing load. This simulation also shows that there are losses in the system of 190,811 kW so it is necessary to add a capacitor bank component with a capacity of 1 MVAR to improve the power factor in the network.